Response kinetics of tethered Rhodobacter sphaeroides to changes in light intensity. - Berry, R M (2000)
Rhodobacter sphaeroides can swim toward a wide range of attractants (a process known as taxis), propelled by a single rotating flagellum. The reversals of motor direction that cause tumbles in Eschericia coli taxis are replaced by brief motor stops, and taxis is controlled by a complex sensory system with multiple homologues of the E. coli sensory proteins. We tethered photosynthetically grown cells of R. sphaeroides by their flagella and measured the response of the flagellar motor to changes in light intensity. The unstimulated bias (probability of not being stopped) was significantly larger than the bias of tethered E. coli but similar to the probability of not tumbling in swimming E. coli. Otherwise, the step and impulse responses were the same as those of tethered E. coli to chemical attractants. This indicates that the single motor and multiple sensory signaling pathways in R. sphaeroides generate the same swimming response as several motors and a single pathway in E. coli, and that the response of the single motor is directly observable in the swimming pattern. Photo-responses were larger in the presence of cyanide or the uncoupler carbonyl cyanide 4-trifluoromethoxyphenylhydrazone (FCCP), consistent with the photo-response being detected via changes in the rate of electron transport.